Intensity of nursing work in a primary healthcare center: An observational study. - Peršolja, Melita (International Journal of Nursing Sciences, 2024)
In the sphere of occupational intensity, nursing stands recognized for its inherently demanding nature, marked by a rapid succession of tasks. Our primary aim was to assess the level of job intensity within nursing by analyzing the frequency and duration of activities performed by nurses, instances of task overlap, and the distribution of break times within a primary healthcare center. This study was conducted using a descriptive working method. Nursing activities were recorded with the observation of six nurses, each monitored for 37.5 h. We used the Maribor System for measuring Quantity in Nursing Care in Primary Health Care Settings to measure the nursing care activities about direct patient care, indirect patient care, and other unproductive aspects through direct non-participant observations. About 41.5% (n = 1,640) of all nursing activities involving direct contact with patients, about 38.2% (n = 1,508) was indirect patient care, where a large amount worked with paper files (n = 666, 16.9%). In addition, about 15.0% were other nursing activities (mostly computer work), and just 5.3% (n = 210) of tasks were unproductive. The observational findings indicate a pronounced level of work intensity experienced by nurses in primary health clinics. Significantly, nurses were predominantly engaged in direct patient care tasks, often managing multiple activities simultaneously. Their transitions between tasks occurred approximately every 3 min, frequently without adequate intervals for breaks. This study highlights the need to shift nurses' focus from a task-centric approach to one centered on patient care. The prevailing emphasis on tasks may contribute to enduring fatigue and professional dissatisfaction. Consequently, there is an urgent need to redefine the scope of a nurse's role and implement a comprehensive computer information system as an integral part of this redefined approach.